Skala Tawakal Kepada Allah : Pengembangan Ukuran-Ukuran Psikologis Surrender To God dalam Perspektif Islam - Ahdha Sartika; Irwan Nuryana Kurniawan (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
This preliminary study aimed to explore the psychometric properties ofSkala Tawakal kepada Allah as psychological measures of Surrender to God in the Islamic perspective. This study involved 224 respondents, 54% female, average age 37years, 81.5% were married, and the average monthly income of IDft 3,000,000.00. Skala Tawakal kepada Allah, together with Surrender To God Scale (Wong, McDonald, and Gorsuch, 2000), Satisfaction with Life Scale (Diener, Emmons, Larsen, and Griffin, 1985), Scale of Positive and Negative Experience (Diener, Wirtz, Tow, Kim-Prieto, Oishi, and Biswas-Diener, 2009) was administered to 224 respondents to evaluate the factor structure, reliability, and validity of the Skala Tawakal kepada Allah. The results of exploratory factor analysis, internal consistency reliability analysis, and correlational analysis with criterion variable supported reliability, structural and concurrent validity of Skala Tawakal kepada Allah has initial psychometric evidence of valid and reliable as a measure of psychological Surrender to God. The findings, limitations, and research recommendations regarding Skala Tawakal kepada Allah are briefly discussed. Keyword; Skala Tawakal kepada Allah, Surrender to God,Psychometric properties.